2018
DOI: 10.1021/acs.jmedchem.8b00734
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of the Hydrophobic Chain as a Molecular Switch: Discovery of Capsaicin Derivatives and Endogenous Lipids as Potent Transient Receptor Potential Vanilloid Channel 2 Antagonists

Abstract: The transient receptor potential vanilloid type-2 (TRPV2) protein is a nonselective Ca permeable channel member of the TRPV subfamily, still considered an orphan TRP channel due to the scarcity of available selective and potent pharmacological tools and endogenous modulators. Here we describe the discovery of novel synthetic long-chain capsaicin derivatives as potent TRPV2 antagonists in comparison to the totally inactive capsaicin, the role of their hydrophobic chain, and how the structure-activity relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Interestingly, Leap2 expression was significantly and positively correlated with the ileal mRNA levels of Ppara , Faah , and Gde1 , but not Abhd6 , and negatively with those of Plcb1 and Trpv2 , but not Cnr2 and Pparg ( Figure 7 ). These correlations might suggest the implication of the eCBome, and in particular, of NAEs—which are biosynthesized through GDE1 (among other enzymes) and (like N -acyl-glycines) are degraded by FAAH, and act as agonists at PPARα (as in the case of OEA and PEA, similar to N -acyl-glycines) and PPARγ (as in the case of AEA) and/or antagonists at TRPV2 (as in the case of OEA and N -linoleoyl-ethanolamine [LEA]) [ 7 , 24 , 25 ]—in Leap2 up-regulation during the development of HFHS-induced glucose intolerance and obesity. The negative correlation with Plcb1 might suggest instead the existence of a negative correlation with 2-MAGs, of whose biosynthesis this enzyme catalyzes the rate-limiting step.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Leap2 expression was significantly and positively correlated with the ileal mRNA levels of Ppara , Faah , and Gde1 , but not Abhd6 , and negatively with those of Plcb1 and Trpv2 , but not Cnr2 and Pparg ( Figure 7 ). These correlations might suggest the implication of the eCBome, and in particular, of NAEs—which are biosynthesized through GDE1 (among other enzymes) and (like N -acyl-glycines) are degraded by FAAH, and act as agonists at PPARα (as in the case of OEA and PEA, similar to N -acyl-glycines) and PPARγ (as in the case of AEA) and/or antagonists at TRPV2 (as in the case of OEA and N -linoleoyl-ethanolamine [LEA]) [ 7 , 24 , 25 ]—in Leap2 up-regulation during the development of HFHS-induced glucose intolerance and obesity. The negative correlation with Plcb1 might suggest instead the existence of a negative correlation with 2-MAGs, of whose biosynthesis this enzyme catalyzes the rate-limiting step.…”
Section: Resultsmentioning
confidence: 99%
“…35 Moriello et al (2018) used the HATU reagent to obtain N-AVAM capsaicin analogues. 36 The starting material for the synthesis was the relevant fatty acyl methyl esters. The fatty acyl methyl esters were hydrolyzed to yield the corresponding fatty acid, which was then reacted with 12 (in the presence of DIPEA in anhydrous DMF) using the azabezotriazole based coupling agent HATU to obtain robust yields of N-AVAM capsaicin analogues.…”
Section: Isolation Of N-avam Capsaicinmentioning
confidence: 99%
“…The fatty acyl methyl esters were hydrolyzed to yield the corresponding fatty acid, which was then reacted with 12 (in the presence of DIPEA in anhydrous DMF) using the azabezotriazole based coupling agent HATU to obtain robust yields of N-AVAM capsaicin analogues. 36 Scheme 12 shows the schema of this coupling reaction using oleic acid (23) as an example reactant for the reaction. The reaction of 23 with 4-hydroxy-3vanillylamine (in the presence of HATU) yields 5.…”
Section: Isolation Of N-avam Capsaicinmentioning
confidence: 99%
“…Unfortunately, these compounds also activated TRPV1 and are thus still not specific. 66 Although these first explorative studies have shown the usefulness in drug design, the current structures are not of a high enough resolution to genuinely push this field forward.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%